2016
DOI: 10.4172/2329-8901.1000155
|View full text |Cite
|
Sign up to set email alerts
|

Antidiarrheal and Antinociceptive Effects of a Probiotic Mixture in Rats

Abstract: Probiotics have been shown to have preventive and therapeutic effects on diarrhea. Because effects tend to be strain specific, benefit of a strain or mixture has to be substantiated by experimental evidence. The aim of this study was to investigate the antidiarrheal and antinociceptive effects of a probiotic mixture (Lactibiane Imedia ® , PiLeJe). Castor oil-induced diarrhea test was performed in Wistar rats following oral administration of probiotics (20 × 10 9 , 30 × 10 9 or 40 × 10 9 CFU/kg), loperamide (5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Castor oil induces intestinal mucosa irritation, inflammation and prevents fluid and electrolytes absorption leading to diarrhea ( Holowacz et al, 2016 ). Few probiotics have been tested using this model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Castor oil induces intestinal mucosa irritation, inflammation and prevents fluid and electrolytes absorption leading to diarrhea ( Holowacz et al, 2016 ). Few probiotics have been tested using this model.…”
Section: Discussionmentioning
confidence: 99%
“… Girard et al (2005a) , observed an antidiarrheal effect of Saccharomyces boulardii attributed to its impact on water and electrolyte secretion. Holowacz et al (2016) showed antidiarrheal effect of a bacterial probiotic mixture through the combination of antimotility and antisecretory properties. Interestingly, B. subtilis CU1 administration displayed preventive effect on castor oil-induced diarrhea resulting in a reduction of water excretion.…”
Section: Discussionmentioning
confidence: 99%